2001
DOI: 10.1097/00002820-200106000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Actual and Perceived Knowledge of Prostate Cancer Among African Americans

Abstract: While digital rectal examination, prostate-specific antigen, and transrectal ultrasound have been identified as effective means of early detection of prostate cancer, African American men tend to underuse these services as compared to white men. Using a nonrandom sample of 108 African American men, the authors conducted an exploratory investigation of the effects of education, income, age, and health insurance coverage on actual and perceived knowledge of prostate cancer. The extent to which the use of prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 1 publication
4
46
0
6
Order By: Relevance
“…Similarly, researchers in the United States, found that exposure to information on prostate cancer positively predicted participation in cancer screening (Nivens et al, 2001). Agho and Lewis (2001) reported that among 108 African-American men, there was a statistically significant relationship between perceived knowledge about prostate cancer and participation in screening (r=0.55, p 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, researchers in the United States, found that exposure to information on prostate cancer positively predicted participation in cancer screening (Nivens et al, 2001). Agho and Lewis (2001) reported that among 108 African-American men, there was a statistically significant relationship between perceived knowledge about prostate cancer and participation in screening (r=0.55, p 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…This echoes research in the USA. 8,10 Although prostate cancer is frequently asymptomatic in the early stages, knowledge of symptoms associated with the disease is essential to encourage early help seeking.…”
Section: Discussionmentioning
confidence: 99%
“…8 A decreased level of knowledge and awareness in African-American men compared with Whites has been observed in several studies in the USA. 7,10 However, this difference may not exist when adjustments are made for variables such as education and age. 8,9 Much of the research to date examining knowledge and beliefs about prostate cancer has been conducted in the USA: limited data exist regarding the awareness of Black men in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Distrust of the medical system, complementary and alternative medicine (CAM) beliefs, poverty, limited education, and prior health experiences contribute to existing disparities in mortality rates (Agho & Lewis, 2001;Farkas, Marcella, & Rhoads, 2000;Jones & Wenzel, 2005;Kendall & Hatton, 2002;Kinney, Emery, Dudley, & Croyle, 2002;Marks, 2002;Wolff et al, 2003). Many African Americans continue to distrust healthcare providers because of prior and continuing unequal healthcare experiences.…”
mentioning
confidence: 99%